Strongly*-2 Divisor Cordial Labeling of Cycle Related Graphs - C. Jayasekaran; V.G. Michael Florance (Ratio Mathematica, 2023)
A strongly*-2 divisor cordial labeling of a graph G with the vertex set V (G) is a bijection a : V (G) → {1, 2, 3, ..., |V (G)|} such that each edge cd assigned the label 1 if the lower integal value of sum of a(c), a(d) and a(c)a(d) divided by 2 is odd and 0 if lower integal value of sum of a(c), a(d) and a(c)a(d) divided by 2 is even, then the number of edges labeled with 0 and the number of edges labeled with 1 differs by atmost 1 or |ea(0) − ea(1)| ≤ 1 where ea(0) denotes the number of edges labeled with 0 and ea(1) denotes the number of edges labeled with 1. A graph which admits a strongly*-2 divisor cordial labeling is called a srongly*-2 divisor cordial graph. In this paper, we prove that the wheel graph Wg and sunflower graph SFg are strongly*-2 divisor cordial graphs.